A telehealth approach to conducting clinical swallowing evaluations in children with cerebral palsy. (August 2016) - Kantarcigil, Cagla; Sheppard, Justine Joan; Gordon, Andrew M.; Friel, Kathleen M.; Malandraki, Georgia A.
Highlights: The first study showing the value of telehealth for evaluating pediatric dysphagia. Asynchronous clinical swallowing tele-evaluations in children with CP are reliable. Inter- and intrarater agreement on dysphagia severity was substantial to excellent. Recordings' quality and pre-training to criterion increase telehealth reliability. Abstract: Background: Accurate and timely evaluation of dysphagia in children with cerebral palsy (CP) is critical. For children with limited access to quality healthcare, telehealth is an option; however, its reliability needs to be investigated. Aim: To test the reliability of an asynchronous telehealth model for evaluating dysphagia in children with CP using a standardized clinical assessment. Methods and procedures: Nineteen children (age range 6.9–17.5) were assessed at three mealtimes via the Dysphagia Disorder Survey (DDS) by three clinicians (face-to-face evaluations). Mealtimes were video-recorded to allow asynchronous evaluations by a remote clinician who also completed approximately 1/3 of face-to-face evaluations. Agreement was tested on DDS variables and dysphagia severity. Outcomes and results: Results revealed substantial to excellent agreement between face-to-face and remote assessments by the same rater (78–100%, KW  = 0.64–1) on all, but two variables (oral transport and oral pharyngeal swallow) and by different raters (69–89%, KW  = 0.6–0.86) on all but one variable (orienting). For dysphagia severity, intrarater agreement was excellent (100%, KW  = 1); interrater agreement was substantial (85%; KW  = 0.76). Conclusions and implications: Asynchronous clinical swallowing evaluations using standardized tools have acceptable levels of agreement with face-to-face evaluations, and can be an alternative for children with limited access to expert swallowing care.